Ingestão regular do suco de laranja vermelha reduz pressão arterial de adultos - Lima, Cláudia Gonçalves de [UNESP]; Basile, Lívia Gussoni; Silveira, Jacqueline Queiroz da [UNESP]; Cesar, Thais Borges [UNESP] (My University, 2012)
Objective – This study aimed to investigate the regular ingestion of red orange juice on blood pressure, anthropometric and diet variables of adults. Methods – The individuals in the experimental group, composed by 19 men and 16 women received 750 mL / d of pasteurized red orange juice for 8 weeks. All volunteers were evaluated for anthropometric, dietary and hemodynamic parameters in the beginning and at the end of the experimental period. Results – There was no change in the variables anthropometric after ingestion of red orange juice. The systolic blood pressure reduced significantly among eutrophic participants supplemented with red orange juice and the diastolic blood pressure reduced among the pre-obese participants. There were significant increases in vitamin C and folate intakes during the experimental period. Conclusion – Regular consumption of red orange juice has shown hypotensive properties, suggesting cardiovascular protective activity in adults. So it would be beneficial to encourage the consumption of citrus fruits as they are unique dietary sources of flavanones.

Objetivo – Investigar a ingestão regular do suco de laranja vermelha sobre a pressão arterial, variáveis antropométricas e dietéticas de indivíduos adultos. Métodos – Os indivíduos do grupo experimental, formado por 19 homens e 16 mulheres, receberam 750 mL/dia de suco de laranja vermelha pasteurizado durante 8 semanas. Foram realizadas avaliação antropométrica, dietética e hemodinâmica. Todas as avaliações foram realizadas no início do período experimental e após o tratamento dietético com o suco de laranja. Resultados – Não houve alteração nas variáveis antropométricas após a ingestão do suco de laranja vermelha. A pressão arterial sistólica reduziu significativamente entre os participantes eutróficos que consumiram suco de laranja vermelha e a diastólica reduziu entre os participantes com excesso de peso. Houve aumento significativo da ingestão de vitamina C e folato durante o período experimental. Conclusão – O consumo regular do suco de laranja vermelha mostrou propriedade hipotensora, sugerindo atividade protetora cardiovascular em indivíduos adultos. Portanto, seria interessante incentivar o consumo de frutas cítricas, pois são exclusivas fontes dietéticas de flavanonas.
Regular intake of red orange juice reduces blood pressure in adults
Keywords: Juices; Blood pressure; Body weight; Sucos; Pressão arterial; Peso corporal